2022
DOI: 10.3389/fnana.2022.844171
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Neurons in the Brain and Gnathal Ganglion of Larval Spodoptera frugiperda

Abstract: The fall armyworm Spodoptera frugiperda (S. frugiperda) (Lepidoptera: Noctuidae) is a worldwide, disruptive, agricultural pest species. The larvae of S. frugiperda feed on seedling, leave, and kernel of crops with chewing mouthparts, resulting in reduced crop yields. Serotonin is an important biogenic amine acting as a neural circuit modulator known to mediate lots of behaviors including feeding in insects. In order to explore the serotonergic neural network in the nervous system of larval S. frugiperda, we pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…The 5HT-IR cells localised in the SOG share a high similarity with the clusters reported for the closely related species M. sexta, H. armigera and S. frugiperda (Griss 1989;Tang et al 2019;Zhang et al 2022). In our findings for S. exigua compared to H. armigera, the AL resembles the GNG-L1, VPL-1 has resemblance in localisation with GNG-L2, our VPL-2 has resemblance with the GNG-L3, DAM resembles the location of GNG-AD and even the less frequently found VC cluster from our study resembles GNG-AV (Tang et al 2019).…”
Section: Ht Immunoreactivitysupporting
confidence: 71%
See 2 more Smart Citations
“…The 5HT-IR cells localised in the SOG share a high similarity with the clusters reported for the closely related species M. sexta, H. armigera and S. frugiperda (Griss 1989;Tang et al 2019;Zhang et al 2022). In our findings for S. exigua compared to H. armigera, the AL resembles the GNG-L1, VPL-1 has resemblance in localisation with GNG-L2, our VPL-2 has resemblance with the GNG-L3, DAM resembles the location of GNG-AD and even the less frequently found VC cluster from our study resembles GNG-AV (Tang et al 2019).…”
Section: Ht Immunoreactivitysupporting
confidence: 71%
“…Regarding the projections and commissures, TA-IR and 5HT-IR were the most similar. The locations of the observed cell bodies and projections are similar in location and number to those in CNSs of other insect species, but mostly to the instars of closely related lepidopteran species (Granger et al 1989;Tang et al 2019;Zhang et al 2022). Combining the results of locations of the biogenic amines and their rate limiting enzymes with the location of AcMNPV in the CNS of mid third instar S. exigua larvae, there does not seem to be a one to one overlap between virus and location of the biogenic amine-producing in exactly the same cell bodies (Figure 2).…”
Section: Biogenic Amines and Parasites Location In The Cns Of Larval ...mentioning
confidence: 52%
See 1 more Smart Citation
“…An interesting research found that starved male cells consume their own proteins ( 33 ). Serotonergic neurons in the brain of larval S. frugiperda are involved in multiple effects in a variety of behaviors, like feeding-related modulation ( 34 ). The stress caused by dsRNA administration may have triggered the nervous system to promote this cannibalism; excluding the cannibalism of 1 st instar, one-time feeding kills individual larva in 1 st and 2 nd instar.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the expression pattern of TRH in D. melanogaster(Neckameyer et al, 2007), BdorTRH was mainly distributed in neural tissues. Although studies on serotonin distribution in the central nervous system of several insect species have been made possible by the availability of specific antibodies against 5-HT(Huser et al, 2012;Tang et al, 2019;Zhang et al, 2022), the expression pattern of neuronal TRH in insects is largely unknown. Our study on the metamorphosis of the TRH-IR system has revealed that, in general, the organisation of neuronal TRH cell clusters persists toF I G U R E 5 Expression pattern of BdorTRH in 15-day-old adult neural tissues based on anti-V5 staining.…”
mentioning
confidence: 99%